The implementation of Reading to Learn for the Southern Thailand pre-service teachers - Monaliza Hernandez Mamac; Lungguh A. Bangga (Indonesian Journal of Applied Linguistics, 2023)
For English as a Foreign Language learners, writing is often considered a difficult skill to grasp with. Studies show that both EFL learners and teachers face similar challenges in developing EFL writing ability. This includes inadequate exposure to English, class size, insufficient knowledge of how language works in context, and mother tongue interferences which are believed to be the major challenges for both learners and teachers. This paper reports on an action research project aiming to identify the overall development of pre-service teachers’ skills in writing discussion texts and explore how the Reading to Learn (R2L) intervention helps these teachers develop their control over the target genre. Under the R2L approach, thirty (30) second-year teachers majoring in English language teaching at the Prince of Songkla University, Pattani Campus involved in the study. Results of the study suggest that the teachers writing skill gap was relatively neutralised after the intervention. In addition, the development of the pre-service teachers’ control over the target genre and language features is evident in text analysis. Upon the intervention, it is found that the teachers developed better control of the features of the discussion genre. Specifically, they developed their control over the stages, phases, appraisal resources, and periodicity which are crucial to establishing well-presented rhetorical features of a discussion text. In relation to the results, some recommendations are proposed for further research, including applying R2L intervention program in the mainstream education in Thailand.